2013
DOI: 10.3109/00016489.2013.797602
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation surgery in patients with narrow facial recess

Abstract: Among the 39 cases, the narrowest distance between the facial nerve and the chorda tympani nerve was less than 1.0 mm. All patients successfully underwent cochlear implantation surgery. No injuries of the facial nerve, chorda tympani nerve, or the posterior wall of the auditory canal were reported in any of the patients. There were significant differences in the injuries of the facial nerve, chorda tympani nerve, and posterior wall of the auditory canal in these cases compared with previous approaches to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Both approaches started with a postauricular incision followed by a mastoidectomy. In the facial recess approach, the facial nerve was skeletonized and the facial recess was opened as wide as possible, then the chorda tympani nerve was exposed and moved anteriorly to widen the facial recess [20]. The cochleostomy was made in the area where the round window niche is normally situated.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Both approaches started with a postauricular incision followed by a mastoidectomy. In the facial recess approach, the facial nerve was skeletonized and the facial recess was opened as wide as possible, then the chorda tympani nerve was exposed and moved anteriorly to widen the facial recess [20]. The cochleostomy was made in the area where the round window niche is normally situated.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Wang L et al and Wang LE et al, in their studies, found 32 patients with narrow FRs of less than 1.0 mm. 36 37 The main reason for the narrow FR, according to them, was CTN retropositioning.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of the bone overlying the chorda tympani may prevent this complication, and yet skeletonization of the structure is required to optimize visualization of the round window [28]. In patients with a narrow facial recess, some surgeons may suspend, place anteriorly, or adhere the chorda tympani nerve to the posterior wall of the auditory canal in order to expose the round window and preserve the function of chorda tympani nerve [30]. …”
Section: Discussionmentioning
confidence: 99%